Electromagnetic Catalytic Cracking Process of Vacuum Residue Using Fe2O3/Al2O3 - Metta Wijayanti; Sri Haryati; Muhammad Djoni Bustan (Sriwijaya Journal of Environment, 2020)
Vacuum residue well know as waste product from refinery crude oil refinery and need a further process  to improve its quality. In this study, a catalytic cracking process of vacuum residue in electromagnetic field is investigated using Fe2O3/Al2O3 as catalyst. The optimization process is conducted by combination vacuum residue and catalyst in the ratios of 1:5, 1:6, 1:7, 1:8, and 1:9 under 75 min of reaction time, 400oC and 10A applied current . Liquid product analyzed using gas cromatografy mass spectrometry (GCMS). The result showed that there were a formation of, p-xylene, paraffin, and naphthalene  detected, meaning it was successfully cracked.  In the retention time 4,3min, identified p-xylene which aromatic groups about 11,38%. Not only  1,04% paraffin identified in the retention time 7,76 min. But also,  naphtalene about 3,28% was identified in the retention time 7,80 min.